Extracellular vesicles and preterm infant diseases - Chen, Wenqain; Kongsomros, Supasek; Thorman, Alexander; Esfandiari, Leyla; Morrow, Ardythe L.; Chutipongtanate, Somchai; Newburg, David S. (Frontiers in Pediatrics, 2025)
With the continuous improvement in perinatal care, the number of viable preterm infants is gradually increasing, along with the rise in preterm-related diseases such as necrotizing enterocolitis, bronchopulmonary dysplasia, perinatal brain injury, retinopathy of prematurity, and sepsis. Due to the unique pathophysiology of preterm infants, diagnosing and treating these diseases has become particularly challenging, significantly affecting their survival rate and long-term quality of life. Extracellular vesicles (EVs), as key mediators of intercellular communication, play an important regulatory role in the pathophysiology of these diseases. Because of their biological characteristics, EVs could serve as biomarkers and potential therapeutic agents for preterm-related diseases. This review summarizes the biological properties of EVs, their relationship with preterm-related diseases, and their prospects for diagnosis and treatment. EVs face unique challenges and opportunities for clinical applications.